Analysis of the knowledge of nursing professionals in relation to hygienization of hands - Letícia Morgana Bertholdo de Souza; Mariana Fröhlich Alievi; Caroline Zottele Piasentin; Vanessa Adelina Casali Bandeira; Marli Maria Loro; Eniva Miladi Fernandes Stumm; Adriane Cristina Bernat Kolankiewicz (Revista de Epidemiologia e Controle de Infecção, 2018)
Background and Objectives: Given the importance of the knowledge and practice of hand hygiene in the perspective of nursing, we aimed to analyze the knowledge of nursing professionals in the hospital environment about hand hygiene. Methods: This is a cross-sectional study which was developed with 159 nursing professionals. Data were collected through the application of questionnaire "Knowledge Test on Hand Hygiene for health professionals" and then analyzed was descriptive and analytical. Results: The professionals recognized the cross-transmission route of microorganism (96,9%). There was a statistically significant difference between the units regarding the minimum time for alcohol preparation in the actions before the patient's contact (p=0.018), after arriving at the unit after lunch (p=0.014), before applying injection (p=0.077), before emptying the urine (p=0.020) and withdrawing from the patient (p=0.002). Regarding the actions of both units to avoid contamination, presented statistical difference before performing aseptic procedure (p=0.013). Conclusion: the study showed the nursing staff had that the workers had knowledge about the subject, however, it is necessary to produce technologies that allow health professional to rethink their practices since joining the institution.